Analisis Risiko Pada Rantai Pasok Industri Minuman Siap Saji Jus Buah Dengan Pendekatan SCOR-FMEA - Sawarni Hasibuan; Hermawan Thaheer; Joko Supono; Irhamni Irhamni (Universitas Mercu Buana, 2021)
The beverage industry is one of the leading national industries with high growth and a very tight level of competition. The risk supply chain management approach is one of the driving factors for the sustainability of the industrial supply chain. The purpose of this study is to analyze the risk supply chain management to support the sustainability of the beverage industry supply chain in the case of fruit juice beverage products. The data used in this study consisted of primary data and secondary data. Primary data obtained from distributing questionnaires, interviews and field observations. The respondents of this research are the beverage industry supply chain stakeholders. This research combines qualitative and semi-quantitative approaches. Qualitative analysis is conducted to describe activities and risks in the beverage industry supply chain. Risk analysis is carried out using a semi-quantitative approach. The risk evaluation in the supply chain of the fruit juice beverage industry combines the SCOR-FMEA method. The risks that are classified as High and Priority are then analyzed by using the Fishbone Diagram as a reference for formulating risk mitigation strategies for the sustainability of the supply chain for the juice beverage industry.